The organisation of physiotherapy for people with multiple sclerosis across Europe: a multicentre questionnaire survey - Rasova, Kamila; Freeman, Jenny; Martinkova, Patricia; Pavlikova, Marketa; Cattaneo, Davide; Jonsdottir, Johanna; Henze, Thomas; Baert, Ilse; Van Asch, Paul; Santoyo, Carme; Smedal, Tori; Beiske, Antonie Giæver; et al. (BMC health services research, 2016)
BACKGROUND: Understanding the organisational set-up of physiotherapy services across different countries is increasingly important as clinicians around the world use evidence to improve their practice. This also has to be taken into consideration when multi-centre international clinical trials are conducted. This survey aimed to systematically describe organisational aspects of physiotherapy services for people with multiple sclerosis (MS) across Europe. METHODS: Representatives from 72 rehabilitation facilities within 23 European countries completed an online web-based questionnaire survey between 2013 and 2014. Countries were categorised according to four European regions (defined by United Nations Statistics). Similarities and differences between regions were examined. RESULTS: Most participating centres specialized in rehabilitation (82 %) and neurology (60 %), with only 38 % specialising in MS. Of these, the Western based Specialist MS centres were predominately based on outpatient services (median MS inpatient ratio 0.14), whilst the Eastern based European services were mostly inpatient in nature (median MS inpatient ratio 0.5). In almost all participating countries, medical doctors - specialists in neurology (60 %) and in rehabilitation (64 %) - were responsible for referral to/prescription of physiotherapy. The most frequent reason for referral to/prescription of physiotherapy was the worsening of symptoms (78 % of centres). Physiotherapists were the most common members of the rehabilitation team; comprising 49 % of the team in Eastern countries compared to approximately 30 % in the rest of Europe. Teamwork was commonly adopted; 86 % of centres based in Western countries utilised the interdisciplinary model, whilst the multidisciplinary model was utilised in Eastern based countries (p = 0.046). CONCLUSION: This survey is the first to provide data about organisational aspects of physiotherapy for people with MS across Europe. Overall, care in key organisational aspects of service provision is broadly similar across regions, although some variations, for example the models of teamwork utilised, are apparent. Organisational framework specifics should be considered anytime a multi-centre study is conducted and results from such studies are applied.
Keywords: ambulantní péče; Humans; Europe; Inpatients; Prescriptions; Surveys and Questionnaires; Physical Therapy Modalities; techniky fyzikální terapie; Patient Care Team; Referral and Consultation; konziliární vyšetření a konzultace; Evropa; průzkumy a dotazníky; hospitalizovaní pacienti; Ambulatory Care; roztroušená skleróza; Multiple Sclerosis; týmová péče o pacienty; lidé; lékařské předpisy